Pengaruh Pengembangan Destinasi Wisata Terhadap Inovasi Kebijakan Pemerintah Daerah Provinsi Bali - Ida Bagus Kade Subhiksu (Denpasar Institute, 2020)
The change in leadership in developing a responsible tourism strategy and policy should take into account the views of several stakeholders including industry, local communities, special groups representing environmental interests, and tourists themselves. In the context of tourism development and development as a totality of products, namely tourist attraction, accessibility, amenities, and ancillary, community involvement and government policies are needed, so that the dynamics of tourism also have an impact on changes in bureaucratic leadership issues in the formulation and implementation of strategic tourism policies as a result of developments and the development of tourism is particularly related to the innovation of facilities and infrastructure that has been carried out by the Provincial Government of Bali as an effort to transformative leadership in the context of addressing the issue of leadership change. This study uses a quantitative approach using descriptive statistical analysis tools and linear regression to be able to simulate the results of research results by surveying respondents who traveled to several tourist attractions in Bali. The number of respondents in this study amounted to 465 people determined by purposive sampling because the identity and number of the population are unknown. Correlation analysis and linear regression tools are used to produce a description of the results and analysis of the relationship between the developments of Bali's tourism destinations on the issue of leadership change in the strategic policy development of tourism development in Bali. The issue of policy change in the context of the transformative leadership of the provincial government of Bali in making strategic changes should remain by the dynamics of change and the development of the tourism industry in Bali based on the expectations of tourists, local communities, and the business world based on the principle of sustainable development of cultural tourism.